A new approach on treatment of esophageal atresia: uniportal vats for surgical repair – a report of two cases. Issue 2 (April 2018) - Fortes, Lorena M.; González, Miriam G.; Mata, Noelia C.; Ruiz, María R.; Tellado, Manuel G.
Abstract : Esophageal atresia is a rare congenital malformation affecting one in every 3500 live births. Treatment consists in surgical ligation of the fistula and esophageal anastomosis of the two pouches by conventional thoracotomy or by thoracoscopic approach. In recent years, uniportal video-assisted thoracic surgery has been a revolution in thoracic surgery but it had never been used for treatment of congenital pathologies like esophageal atresia. We have used this technique for the treatment of two newborns with this condition. We made a reparation with fistula ligation and end-to-end anastomosis, video-assisted using one only incision. We have excellent results with this technique. A larger list of patients and an increased surgical experience is needed but this can be a new and appropriated alternative in the reparation of esophageal atresia-tracheoesophageal fistula.